University of Latvia - (:unkn) unknown (My University, 2012)
University of Latvia brochure.
Prepared for publication in 2012 by International Relations Department, Public Relations Department, University of Latvia Press.
Keywords: History (University of Latvia); Faculties of the University of Latvia; Research institute (University of Latvia); Centres (University of Latvia); Libraries (University of Latvia); Botanical garden (University of Latvia); Mission statement (University of Latvia); University sports (University of Latvia); Museum of History of Science and Technology